Judges 19-21: The Disasters of the Community of Virtue - Cohen, Richard A. (Religions, 2020)
This paper is an ethical exegesis of the biblical story of Gibeah, which concludes the Book of Judges (19-21), to show the catastrophic failure of the anti-political politics of the “community of virtue”, i.e., the rejection of power for the sake of moral society, such as proposed by libertarians, neo-liberals, anarchists and utopians. I consider Kant’s statement of the political problem: given humanity’s unsocial sociality, where each person is tempted to act as an exception to universal law, humans need rulers, but how to obtain rulers who are not themselves ruled by power, and become tyrannical, rather than being ruled by justice? The solution proposed by “the community of virtue” would reject power altogether and replace it with society regulated exclusively according to the moral virtue of its members. The Bible’s story of Gibeah shows graphically and conclusively the failure of any such attempt. Instead, as with normative political philosophy, the Bible endorses the rule of a king, i.e., the rule of the state, and a politics whereby power is disciplined to serve justice because it is rooted in Torah, i.e., a fundamental covenant, charter or constitution, aware and vigilant regarding the ambiguities and temptations of sovereignty, and therefore, ideally, always open to critique. As exemplified by biblical prophets, political protest against injustices perpetrated by the powerful against the least—widow, orphan, stranger—is at once religious obligation and true patriotism.